Effect of Molecular Architecture of Surface-Active Organosilicon Macromers on Their Colloidal Properties in Relation to Heterophasic Radical Polymerization of Styrene and Methyl Methacrylate - Valeriy Borisovich Gostenin; Anton Mikhailovich Shulgin; Irina Sergeevna Shikhovtseva; Alexandra Alexandrovna Kalinina; Inessa Alexandrovna Gritskova; Vitaliy Pavlovich Zubov (Physchem, 2024)
The effects of the molecular architecture of water-insoluble organosilicon polymerizable surfactant macromers (SAMs) on their colloidal-chemical characteristics and on their efficiency in heterophase radical polymerization of styrene and methyl methacrylate were studied. It was shown that despite considerable differences in the structure of three synthesized oligomers (linear α,ω-dipropylmethacrylatepolydimethylsiloxane with a number of repeated siloxane units n = 20—l-SAM; branched γ-methacryloxypropyl containing dimethylsiloxane oligomer—b-SAM; and “spherical” oligo-(γ-methacryloxypropyl)silsesquioxane—s-SAM), the colloidal-chemical characteristics (interfacial tension, layer thickness, adsorption, etc.) were rather similar. In particular, they all form “thick” multimolecular adsorption layers on the toluene–water interphase. All three SAMs were shown to act as effective colloidal stabilizers in heterophase radical polymerization of styrene and methyl methacrylate, which resulted in one-step preparation of large (0.5–1.5 µm) polymer particles with narrow particle size distribution. The obtained results are consistent with the published data on the use of water-insoluble polymerizable oligomers of various chemical structures on the heterophase radical polymerization. The use of these colloidal stabilizers may be considered as an effective way to obtain stable suspensions with large particles and narrow particle size distribution.